Hypothalamic over-expression of VGF in the Siberian hamster increases energy expenditure and reduces body weight gain - Lewis, Jo E.; Brameld, John M.; Hill, Phil; Cocco, Cristina; Noli, Barbara; Ferri, Gian-Luca; Barrett, Perry; Ebling, Francis J.P.; Jethwa, P.H. (Public Library of Science, 2017)
VGF (non-acronymic) was first highlighted to have a role in energy homeostasis through experiments involving dietary manipulation in mice. Fasting increased VGF mRNA in the Arc and levels were subsequently reduced upon refeeding. This anabolic role for VGF was supported by observations in a VGF null (VGF-/-) mouse and in the diet-induced and gold-thioglucose obese mice. However, this anabolic role for VGF has not been supported by a number of subsequent studies investigating the physiological effects of VGF-derived peptides. Intracerebroventricular (ICV) infusion of TLQP-21 increased resting energy expenditure and rectal temperature in mice and protected against diet-induced obesity. Similarly, ICV infusion of TLQP-21 into Siberian hamsters significantly reduced body weight, but this was due to a decrease in food intake, with no effect on energy expenditure. Subsequently NERP-2 was shown to increase food intake in rats via the orexin system, suggesting opposing roles for these VGF-derived peptides. Thus to further elucidate the role of hypothalamic VGF in the regulation of energy homeostasis we utilised a recombinant adeno-associated viral vector to over-express VGF in adult male Siberian hamsters, thus avoiding any developmental effects or associated functional compensation. Initially, hypothalamic over-expression of VGF in adult Siberian hamsters produced no effect on metabolic parameters, but by 12 weeks post-infusion hamsters had increased oxygen consumption and a tendency to increased carbon dioxide production; this attenuated body weight gain, reduced interscapular white adipose tissue and resulted in a compensatory increase in food intake. These observed changes in energy expenditure and food intake were associated with an increase in the hypothalamic contents of the VGF-derived peptides AQEE, TLQP and NERP-2. The complex phenotype of the VGF-/- mice is a likely consequence of global ablation of the gene and its derived peptides during development, as well as in the adult.